2008
DOI: 10.1161/circulationaha.107.750810
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article, “Off-Pump Versus On-Pump Coronary Artery Bypass Graft Surgery: Differences in Short-Term Outcomes and in Long-Term Mortality and Need for Subsequent Revascularization”

Abstract: We would like to thank Bollati et al for their interest in our study. 1 Their concerns about the validity of our study are (1) that the logistic regression analyses used to risk-adjust the outcomes are based on stepwise models, and (2) that there is no c statistic reported for the propensity model used to test for selection bias.We do not have space for a discussion of the pros and cons of stepwise analyses, but when we developed models based on all available independent variables, the results were almost id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
2
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 2 publications
4
106
2
7
Order By: Relevance
“…The main findings in this study are as follows: (1) landiolol (0.12 mg/kg/min) reduced the three-dimensional motion of the coronary artery on the porcine beating heart; (2) the heart rate was reduced by 10-15% during landiolol infusion, thus leading to a 20-30% reduction in coronary artery motion; (3) in this dose range, the blood pressure, cardiac output, and pulmonary wedge pressure were stable. Landiolol has been developed to have shorter duration of action and a higher b-1 adrenergic receptor selectivity, in comparison with esmolol and propranolol [10].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The main findings in this study are as follows: (1) landiolol (0.12 mg/kg/min) reduced the three-dimensional motion of the coronary artery on the porcine beating heart; (2) the heart rate was reduced by 10-15% during landiolol infusion, thus leading to a 20-30% reduction in coronary artery motion; (3) in this dose range, the blood pressure, cardiac output, and pulmonary wedge pressure were stable. Landiolol has been developed to have shorter duration of action and a higher b-1 adrenergic receptor selectivity, in comparison with esmolol and propranolol [10].…”
Section: Discussionmentioning
confidence: 63%
“…However, there are consistent concerns about the quality of anastomosis and graft patency [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…OPCAB techniques presumably reduce emboli production caused by disruption of atheromatous plaques during cannulation, cross-clamping and manipulation of the ascending aorta. Large retrospective studies have shown OPCAB to be associated with a lower incidence of stroke compared with conventional on-pump CABG [67][68][69][70]. The Japanese Association for Coronary Artery Surgery also reported the stroke incidence of OPCAB performed in 2013 to 0.75 % (50/6650 cases) and that of conventional on-pump CABG to 1.34 % (34/ 2519 cases, P = 0.0315, http://www.jacas.org/enquete/ 2013.html).…”
Section: Off-pump Cabgmentioning
confidence: 99%
“…Die initialen Erwartungen an die Off-pumpChirurgie, nämlich vorrangig ein besseres neurologisches Outcome und ein vermindertes Auftreten von akutem Nierenversagen, konnten anhand der aktuellen Datenlage bislang nicht ausreichend bestätigt werden [8,9,10]. Auch zeigen die Ergebnisse aus Metaanalysen, dass Patienten, die ohne HLM operiert werden, insgesamt keineswegs unbedingt einen besseren Verlauf haben als Patienten, die "onpump" operiert werden.…”
Section: Moderne Koronarchirurgieunclassified